Compressive creep behavior of hot-pressed Mg1.96Al0.04Si0.97Bi0.03. (15th April 2018) - Michi, Richard A.; Kim, Gwansik; Kim, Byung-Wook; Lee, Wooyoung; Dunand, David C.
Abstract: The compressive creep behavior of hot-pressed Mg1.96 Al0.04 Si0.97 Bi0.03, a promising thermoelectric material, is investigated at 500 °C. At stress levels between 81 and 212 MPa, dislocation creep with stress exponent n = 7.6 ± 0.3 is observed. No diffusional creep is observed, likely attributable to a dispersion of 1 μm Bi-, Al-, and O- rich particles which pin grain boundaries. Mg1.96 Al0.04 Si0.97 Bi0.03 exhibits similar creep behavior to previously studied silicides, but is significantly more creep resistant than other thermoelectric materials, PbTe and Bi2 Te3 . This makes Mg1.96 Al0.04 Si0.97 Bi0.03 an excellent material for thermoelectric power generation systems subjected to high stresses and temperatures. Graphical abstract: Unlabelled Image